STABILITY-INDICATING METHOD DEVELOPMENT AND VALIDATION FOR THE ESTIMATION OF ROSUVASTATIN CALCIUM IN BULK AND TABLET FORMULATION BY REVERSE-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY - SAILAJA B; SRAVANA KUMARI K (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present work was focused on the development and validation of reverse-phase high-performance liquid chromatography (RP-HPLC) method which is simple, rapid, precise, accurate, sensitive, economical, and stability indicating for the quantitation of rosuvastatin calcium in bulk and tablet formulation. Methods: The separation was attained on Waters Symmetry C18 column with dimensions 150×4.6 mm, 5 mm particle size employing 0.1% orthophosphoric acid buffer:acetonitrile in the ratio of 55:45% v/v as mobile phase, which was pumped at a rate of 1.0 ml/min and detected at a wavelength of 241 nm. Results: The linearity of the method was demonstrated in the concentration range of 2–12 μg/ml for rosuvastatin calcium with a correlation coefficient (r2) of 0.999, percentage drug recovery was found to be 100.22–101.16%, and percentage relative standard deviation <2. Limit of detection and limit of quantitation values were found to be 0.013 μg/ml and 0.042 μg/ml, respectively, and assay of marketed tablet formulation was found to be 99.76%. Conclusion: The developed RP-HPLC method was found to be simple, specific, sensitive, rapid, linear, accurate, precise, and economical and could be used for regular quality control of rosuvastatin calcium in bulk and tablet formulation.